A New Paradigm of Institutional South–South Cooperation: Arab Strategies in the South Pacific and Their Impact on Global Governance - Hexu, AI (Arab Journal for Sciences and Research Publishing, 2025)
In the context of global transformations in the energy structure, Arab countries and Pacific Island nations are moving toward a new phase of institutional cooperation. This study relies on theories of institutional economics, international institutionalism, and South-South cooperation, using document analysis and comparative studies to illustrate the development of cooperation between the two sides. The study focuses on the UAE, Saudi Arabia, and Qatar in the fields of infrastructure, renewable energy, and diplomacy. Since 2010, the two parties have established cooperation mechanisms that included at least two ministerial conferences, investments exceeding 50 million in renewable energy, and growing financial and trade agreements. By 2022, non-oil trade between the UAE and Pacific Island countries surpassed 100 million, and its solar energy projects contributed to reducing diesel consumption by one million liters annually and cutting CO2 emissions by 2,750 tons. The results indicate that Arab intervention is reshaping the strategic balance in the South Pacific, challenging traditional powers such as China, the United States, and Australia, and presenting a cooperative model between South-South countries. The study suggests a tripartite framework: Emirati technology – Chinese manufacturing – local application, along with the establishment of a permanent secretariat and a climate risk fund. This model provides an institutional contribution to global governance and offers strategic insights for China and other countries in the Indo-Pacific region.